The use of UV‐VIS‐NIR reflectance spectroscopy to identify iron minerals. Issue 9 (November 2013) - Szalai, Z.; Kiss, K.; Jakab, G.; Sipos, P.; Belucz, B.; Németh, T.; Barnaföldi, Gergely Gábor; Forgás‐Dajka, Emese; Kiss, Csaba; Verebélyi, Erika
Abstract Iron minerals – which behave as indicators in earthly and Martian environments – can be identified by UV‐VIS‐NIR reflectance spectroscopy. The aim of this study was to compare the spectra of various soils and sediments all of which contain iron minerals but developed under different environmental conditions. To identify the mineral of the sediments we used the first and second derivatives of the Kubelka‐Munk transformed spectra. According to their iron mineral composition, the analysed samples can be divided into three distinct groups. Goethite refers to the hydromorphic conditions, hematite suffers from the long and intense weathering in leaching environment. In the case of steppe climatic conditions the weathering is so weak that the appearance of pedogenic iron minerals is improbable in these soils. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)